Association of thymidylate synthase polymorphisms with acute pancreatitis and/or peripheral neuropathy in HIV-infected patients on stavudine-based therapy. - Pere Domingo; Maria del Carmen Cabeza; Ferran Torres; Juliana Salazar; Maria del Mar Gutierrez; Maria Gracia Mateo; Esteban Martínez; Joan Carles Domingo; Irene Fernandez; Francesc Villarroya; Esteban Ribera; Francesc Vidal; et al. (PLoS ONE, 2013)
Background Low expression thymidylate synthase (TS) polymorphism has been associated with increased stavudine triphosphate intracellular (d4T-TP) levels and the lipodystrophy syndrome. The use of d4T has been associated with acute pancreatitis and peripheral neuropathy. However, no relationship has ever been proved between TS polymorphisms and pancreatitis and/or peripheral neuropathy. Methods We performed a case-control study to assess the relationship of TS and methylene-tetrahydrofolate reductase (MTHFR) gene polymorphisms with acute pancreatitis and/or peripheral neuropathy in patients exposed to d4T. Student's t test, Pearson's correlations, one-way ANOVA with Bonferroni correction and stepwise logistic regression analyses were done. Results Forty-three cases and 129 controls were studied. Eight patients (18.6%) had acute pancreatitis, and 35 (81.4%) had peripheral neuropathy. Prior AIDS was more frequent in cases than in controls (OR = 2.36; 95%CI 1.10-5.07, P = 0.0247). L7ow expression TS and MTHFR genotype associated with increased activity were more frequent in patients with acute pancreatitis and/or peripheral neuropathy than in controls (72.1% vs. 46.5%, OR = 2.97; 95%CI: 1.33-6.90, P = 0.0062, and 79.1% vs. 56.6%, OR = 2.90, 95%CI: 1.23-7.41, P = 0.0142, respectively). Independent positive or negative predictors for the development of d4T-associated pancreatitis and/or peripheral neuropathy were: combined TS and MTHFR genotypes (reference: A+A; P = 0.002; ORA+B = 0.34 [95%CI: 0.08 to 1.44], ORB+A = 3.38 [95%CI: 1.33 to 8.57], ORB+B = 1.13 [95%CI: 0.34 to 3.71]), nadir CD4 cell count >200 cells/mm(3) (OR = 0.38; 95%CI: 0.17-0.86, P = 0.021), and HALS (OR = 0.39 95%CI: 0.18-0.85, P = 0.018). Conclusions Low expression TS plus a MTHFR genotype associated with increased activity is associated with the development of peripheral neuropathy in d4T-exposed patients.